Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd008666.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A supplementation during pregnancy for maternal and newborn outcomes

Abstract: Analysis 1.1. Comparison 1 Vitamin A alone versus placebo or no treatment, Outcome 1 Maternal mortality.. .. Analysis 1.2. Comparison 1 Vitamin A alone versus placebo or no treatment, Outcome 2 Perinatal mortality.. .. Analysis 1.3. Comparison 1 Vitamin A alone versus placebo or no treatment, Outcome 3 Neonatal mortality.. .. Analysis 1.4. Comparison 1 Vitamin A alone versus placebo or no treatment, Outcome 4 Stillbirth.. .. .. . Analysis 1.5. Comparison 1 Vitamin A alone versus placebo or no treatment, Outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(26 citation statements)
references
References 138 publications
0
25
0
1
Order By: Relevance
“…However, as summarized in a recent systematic review by van den Broek et al (26), maternal vitamin A supplementation can reduce the risks of clinical maternal infection, night blindness, and anemia. In Nepal, where maternal mortality risk and vitamin A deficiency were major problems, dietary supplementation of mothers with vitamin A reduced all-cause mortality related to pregnancy (27).…”
Section: Discussionmentioning
confidence: 99%
“…However, as summarized in a recent systematic review by van den Broek et al (26), maternal vitamin A supplementation can reduce the risks of clinical maternal infection, night blindness, and anemia. In Nepal, where maternal mortality risk and vitamin A deficiency were major problems, dietary supplementation of mothers with vitamin A reduced all-cause mortality related to pregnancy (27).…”
Section: Discussionmentioning
confidence: 99%
“…In babies born prematurely, symptoms of vitamin A deficiency include broncho-pulmonary dysplasia (a form of chronic lung disease). Night blindness is thought to be one of the first signs of vitamin A deficiency, followed by a diminished ability to fight infections especially respiratory and gastro enteric infections 70 . Vitamin A deficiency in pregnancy is known to result in night blindness, to increase the risk of maternal mortality and is associated with premature birth, intrauterine growth retardation, LBW and abruptio placentae.…”
Section: Vitamin Amentioning
confidence: 99%
“…Increased maternal levels of preformed vitamin A (retinoic acid) have been shown to be associated with miscarriage and with malformations involving the central nervous and cardiac systems. A World Health Organization (WHO) expert group consultation concluded that daily doses of up to 10,000 IU (equivalent to 3000 mcg retinol) or 25,000 IU weekly after day 60 are probably safe, especially in areas where vitamin A deficiency is thought to be common 70 .…”
Section: Vitamin a Supplementationmentioning
confidence: 99%
“…As a consequence, the Cochrane Editorial Unit and 5 CRGs were commissioned to complete or update 12 reviews relating to vitamin A in advance of the guidelines process relating to the vitamin based on questions in the PICO format identified by a panel of experts identified by the WHO micronutrients group (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Since the work on vitamin A was completed, the Cochrane Editorial Unit has also contributed to work on other guidelines programs, including those on iron.…”
Section: What Is the Cochrane Collaboration?mentioning
confidence: 99%